DESKRIPSI DAMPAK PANDEMI COVID-19 TERHADAP PROSES PEMBELAJARAN DARI RUMAH DI KOTA PALOPO - Samsinar Samsinar; Widyawanti Rajiman (Jurnal Muara Pendidikan, 2022)
This study aims to provide an overview of the influence of the covid-19 pandemic on the learning process from home in Palopo City. This research is a descriptive research with a quantitative approach. The results of this study show that Covid-19 has a significant impact on the learning system in elementary and junior high schools in Palopo City. There are negative and positive impacts of Covid-19 on the learning system in schools; 2. Parents gave a negative response to online learning during the study period from home due to several factors; 3. Elementary school parents have a higher response rate than parents who have children at the junior high school level; 4. Parental involvement during learning from home is very high. The data shows that 58% always, 29% often, 11% rarely and 2% never get involved and play a role during learning from home; 5. The involvement of elementary school parents is higher than the involvement of parents who have children at the junior high school level